Effect of seed layers on structure of self-organized Ag nanodots on MgO substrates. (21st May 2015) - Kamiko, Masao; Suenaga, Ryo; Koo, Jung-Woo; Nose, Kenji; Kyuno, Kentaro; Mitsuda, Yoshitaka; Ha, Jae-Geun
Abstract: The influence of 1.0–5.0-nm-thick Ti and Fe seed layers on self-organized Ag nanostructures grown on MgO(001) substrates after annealing was investigated and compared. Atomic force microscopy results indicated that the insertion of Ti and Fe seed layers between the substrate and Ag promoted thermal agglomeration, thereby resulting in the formation of a nanodot array. Moreover, the size and spacing of the Ag/Ti and Ag/Fe nanodots changed significantly and irregularly, respectively, with increasing thickness of the seed layers. X-ray diffraction measurements revealed that the insertion of the Ti seed layer promoted epitaxial growth of Ag nanodots; Ag/Fe nanodots, in contrast, grew non-epitaxially. Based on the results, it can be concluded that the differences between the effects of the Ti and Fe seed layers are mainly due to the thermal equilibrium state between the seed layer elements and Ag.